The Frequency of Antenatal Care with The Risk of Failure to Breastfeeding for Infants Aged 3-6 Months - Indah Yun Diniaty Rosidi; Arisna Kadir (STIKes Patria Husada Blitar, 2021)
Antenatal care during pregnancy has an influence on fetal growth and a mother's readiness to prepare for labor and breastfeeding. Failure to provide exclusive breastfeeding can have a potential death impact on children, because exclusive breastfeeding is the basis for children's survival and children's health because of the irreplaceable nutritional content of breast milk for children's growth and development. This study aimed to determine the correlation between ANC frequency and the risk of breastfeeding failure to infants aged 3-6 months. The study method used Analytical Study with the Case Control approach. The sample in this study was 20 mothers who had babies aged 3 months and were divided into 2 groups, namely the case group and the control group with purposive sampling technique. In this study, cases and controls were not matched. The data analysis used the Fisher Extact test and the odds ratio of case exposure was indicated by a value of Ï <0.05 and an OR value> 1 to determine the amount of risk that occurred in the variable. The results showed that there was no correlation between ANC frequency and failure to administer breast milk for infants aged 3-6 months. The frequency of ANC that was incomplete could have a risk of failure of breastfeeding in infants aged 3-6 months by 2.333 times compared to mothers with the frequency of complete ANC. It is hoped that this study can be continued by paying attention to confounding factors and seeing the correlation between variables.